2018
DOI: 10.1021/acssuschemeng.8b02347
|View full text |Cite
|
Sign up to set email alerts
|

Deodorization by Solar Steam Distillation of Rosemary Leaves Prior to Solvent Extraction of Rosmarinic, Carnosic, and Ursolic Acids

Abstract: This study aims total valorization of rosemary for food applications, moving toward developing an original biorefinery concept using solar steam distillation (SSD) to extract essential oil while preserving active compounds in the raw material, mainly antioxidants, for a further extraction. The deodorization process is important to avoid the extraction of antioxidants with strong aromas which limit their utilization for food preservation. The SSD process was compared with conventional steam distillation (CSD) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Similar results were reported in numerous studies ,, for melissa, peppermint, rosemary, cumin, and cloves where it was found that solar and conventional extractions provide similar essential oil yields with a negligible deviation. It was established in previous work that the solar extraction efficiency is affected by both the daily solar radiation and the cloud cover density since the solar reflector only uses direct radiation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were reported in numerous studies ,, for melissa, peppermint, rosemary, cumin, and cloves where it was found that solar and conventional extractions provide similar essential oil yields with a negligible deviation. It was established in previous work that the solar extraction efficiency is affected by both the daily solar radiation and the cloud cover density since the solar reflector only uses direct radiation.…”
Section: Resultssupporting
confidence: 90%
“…The solar apparatus for the hydro-distillation extraction of orange peels is placed in the National Centre for Studies and Research on Water and Energy at Cadi Ayyad University (Marrakech, Morocco) Figure shows the solar system mainly composed of a 10 m 2 solar reflector coupled to a hydro-distillation unit; each component has numerous specific characteristics.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…While the mass yield in EO is 0.83%, slightly higher than 0.82% that found by Hilali with the same solar system (Hilali et al 2018).…”
Section: Efficiency Of the Solar Distillation Systemmentioning
confidence: 51%
“…As shown in Table 3, the quantities of EOs recovered are 17, 35, and 50 mL, and essential oil extraction yields are 0.85%, 0.88%, and 0.83%, respectively, for 2, 4, and 6 Kg of AMPs, slightly higher than 0.82% that found by Hilali with the same solar system (Hilali et al 2018).…”
Section: Variation Effect Of Some Measured Quantitiesmentioning
confidence: 68%
“…However, these techniques are unsuitable for RA extraction because RA is unstable and sensitive to heat, which degrades RA and lowers its biological activity (Barbieri et al, 2020). Furthermore, the Soxhlet extraction needs a long time (>10 hr) and consumes high energy (Hilali et al, 2018). Consequently, microwave-and ultrasound-assisted extraction methods have been developed for RA extraction (Bellumori et al, 2016;Jacotet-Navarro et al, 2015).…”
mentioning
confidence: 99%